A needs analysis on the utilization of learning management systems as blended learning media in elementary school - Zainil, Melva; Helsa, Yullys; Sutarsih, Cicih; Nisa, Sahrun; Sartono; Suparman (Journal of Education and e-Learning Research, 2024)
In Indonesia, educational activities have shifted to home-based learning after the COVID-19 epidemic broke out. Consequently, digital learning has become a necessary option for many teachers. This study aims to understand teachers’ experiences, digital platform mastery, digital-based learning pedagogy and the role of parents in learning at home in implementing the teaching process using learning management system-based blended learning media during the COVID-19 epidemic. A questionnaire was used in this study to gather data on the experiences of the teachers, parents' participation in home learning during COVID-19, the digital pedagogy and the mastery of digital platforms using a qualitative approach. This study involved 16 students’ parents and 96 elementary school teachers. The data was analyzed using NVivo Pro software. The testing of data validity was carried out through data triangulation. Results of this recent study revealed that based on their experience, teachers still used videos as the main teaching material in digital learning and they carried out the learning assessment process using digital platforms. This was impacted by the process of changing from distant learning to the new normal. Additionally, the selection of digital media was carried out by considering media effectiveness, the learning process, available facilities and digital literacy. Moreover, parents not only provided learning facilities at home but were also more active as facilitators and supervisors during the learning process at home. This study contributes to provide some considerations for mathematics teachers in designing learning management system-based blended learning media in elementary schools during the COVID-19 epidemic.